KEADAAN JALAN SARAD DAN POHON DITEBANG PADA TEGAKAN TINGGAL DI KAWASAN SEBUAH PERUSAHAAN HUTAN DI RIAU - Jurnalis Thaib; Sona Suhartana (Pusat Penelitian dan Pengembangan Hasil Hutan, 1991)
An investigation of skidding performance was conducted at one Forest company in Riau, in 1988. The results showed that stand density rangea from 126 to 190 trees with an average of 158 trees/ha, soft soil .without any rock, land slope ranges from 6,8 to 20,0 % and the trees felled from 2 to 8 with an average of 5 trees/ha. Also it was found that the length of productive skidding road ranges from 91,0 m to 329,8 m with an average of 210,4 m /ha while the length of unprodue- tive skidding road vanes from 2,5 m to 49,9 m with an average of 26,2 m/ha. The ratio between the lengths of unproductive and productive skidding road is 12,5 %. By considering tractor's life time 20.000 hours, around 2.500 hours of them are unproductiue, Relating this figure with owning and operating costs, those unproductive skidding road surely cause quite large loss. Besides, the unproductive tractor movements also cause land exposure to the amount of 122,5 m2/ha. All the above disadvantages can be minimized by planning akidding roads ahead and strictly controlling the operation.